Attracting Customers Online : Effectiveness of Online Marketing Tools - Efendioglu, Abdulkadir; Igna, Fabiola (2011)
Recent developments on internet have created new possibilities of doing business and communicating with customers. And these technology developments have led to the foundation of e-commerce. E-commerce sales kept growing in the recent years and it has been foreseen by researchers that this growth will continue even more in the next years. Consumer behavior online has changed as well and online users have become all-powerful, due to large numbers and promiscuous – consumers visit a lot of websites, but purchase from just a few. Also, the new social consumer uses the internet to be connected and receive information. As a result, internet became a new intermediary between companies and their customers. It is already acknowledged as an important marketing communication channel competing with the traditional ones, such as TV, Magazines, and Radio. Internet provides different ways of online communications with different communication tools that need a better judgment of their effect on consumer communication. The purpose of our thesis is to provide a better understanding on the effectiveness of each online marketing communication tools. In order to reach the purpose of this study our conceptual framework is designed based on earlier studies. A mix of qualitative and quantitative method and case study was chosen. In order to collect data face-to-face semi-structured interviews are held with sixteen students of Luleå University of Technology. The findings of this study showed that customers are conscious about online marketing communication activities and efficiency of the online marketing communication tools are effected by the attributes towards this tools. These tools can be successful at leading for positive outcomes and attracting new visitors to the website if adopted correctly. We have discovered that ‘entertaining’ and ‘trustworthy’ are the most important attributes in online communication and will make any B2C communication successful. Validerat; 20110519 (anonymous)